Altered natural killer cells subsets distribution in children with hepatitis C following vertical transmission. Issue 1 (16th October 2015) - Indolfi, G.; Mangone, G.; Moriondo, M.; Serranti, D.; Bartolini, E.; Azzari, C.; Resti, M.
Summary: Background: Natural killer (NK) cells number, phenotypes and function have been evaluated in many studies in adults with hepatitis C as compared with healthy controls or dynamically during interferon‐based and interferon‐free treatments. Overall, in adults with chronic infection number of circulating NK cells has been reported to be lower when compared to spontaneous resolvers and healthy subjects. Different studies yielded inconsistent findings due to patient and virus heterogeneity. Aim: To evaluate NK cells in children according to the different outcomes of the infection. Methods: In this cross‐sectional study, we examined numbers and phenotypes of circulating NK cells from a homogenous cohort of Italian children with vertically acquired hepatitis C. Results: We compared 31 children who developed chronic infection with nine who presented spontaneous clearance and 13 controls. CD56 + CD3 − NK cell numbers were consistently lower in the persistently infected group ( P  = 0.03 and 0.04). This decrease was due to depletions of CD56 dim NK cells ( P  = 0.03 chronic infection vs. spontaneous clearance), while CD56 bright NK cells were expanded ( P  = 0.03). No significant difference was found in the frequencies of CD56 + CD16 + and CD56 dim CD16 − cells. Perforin expression was higher in children with chronic infection ( P  = 0.03 vs. spontaneous clearance). Conclusions: Altered NK cells number and phenotypes could impact the outcome of HCV infection in children following vertical transmission. This study suggests for the first time that NK cells cytolytic function, featured by CD56 dim cells, contributes to the elimination of HCV in children presenting spontaneous clearance.